Clinical and cost-effectiveness of pharmacogenomic testing for anthracycline-induced cardiotoxicity in childhood cancer: a systematic review and meta-analysis - Wong, Ling Yin Fritz; Sutcliffe, Alastair G.; Ho, Carmen Lok Tung; Lu, Yan; Williams, Carrie L.; Afzal, Faiza; Purkayastha, Mitana (Frontiers in Pharmacology, 2025)
BackgroundAnthracyclines are widely used paediatric chemotherapy drugs, but anthracycline-induced cardiotoxicity (ACT) can cause heart failure in 16% of children. Previous studies have linked genetic variants to ACT and proposed pharmacogenomic testing for anthracycline-treated children; however, this approach remains unrealised. Therefore, this systematic review and meta-analysis evaluates the effectiveness of pharmacogenomic testing for ACT in childhood cancer.MethodsNine bibliographic databases, three trial registers, reference lists and conference abstracts were searched from inception until October 2024. Two reviewers independently performed study selection, data extraction and quality assessment. Clinical effectiveness was defined as: 1) genetic associations, assessed using random-effects meta-analyses of odds ratios (OR) and mean differences (MD) with 95% confidence intervals (CI) for variants examined in ≥2 studies; and 2) prediction accuracy, measured using area under the receiver operating characteristic curve (AUC) of pharmacogenomic models. Cost-effectiveness was assessed using incremental cost-effectiveness ratio (ICER).ResultsAmong 1,215 de-duplicated records, we included 37 clinical effectiveness studies (26,446 patients). Five cardiotoxic (ABCC2 rs8187710, ETFB rs79338777, GPR35 rs12468485, HNMT rs17583889 and UGT1A6 rs17863783; pooled OR range 1.84–6.12; CI range 1.04–18.56) and two cardioprotective (GSTA2 rs2180314 and HFE rs1799945; pooled OR range 0.62–0.63; CI range 0.46–0.84) variants were significantly associated with ACT. Another cardioprotective variant, ABCC5 rs7627754, increased left ventricular ejection fraction (MD 7.39%; CI 4.63%–10.14%) and fractional shortening (MD 5.04%; CI 2.00%–8.08%). Pharmacogenomic models using clinical and genetic variables (AUC range 0.67–0.87) showed higher accuracy in predicting ACT than those using clinical variables (AUC range 0.57–0.81) across five studies. We identified only one cost-effectiveness study (100 patients), showing one of these models reduced costs (−5.7%) and mortality (−17%) compared to standard care (ICER-negative). Overall, the evidence was graded as very-low-certainty across all outcomes due to imprecision, inconsistency and publication bias.ConclusionDespite promising results, this review highlights the lack of robust evidence to support pharmacogenomic testing for ACT in children. Further cost-effectiveness studies and ethnically diverse prediction models are needed to demonstrate the impact of pharmacogenomic testing on ACT prognosis and clinical decision-making prior to adoption.Systematic Review RegistrationPROSPERO identifier CRD42024557946.